2008
DOI: 10.1080/17483100801904069
|View full text |Cite
|
Sign up to set email alerts
|

The Lyon Brace

Abstract: The Lyon Brace or adjustable multi-shells brace has been used for more than 60 years. Three types of braces have been developed: Lyon thoracic brace, Lyon thoraco lumbar brace and Lyon lumbar brace. Considering the conservative orthopaedic treatment of scoliosis we outline the results of this orthosis. The management of the Lyon Brace includes: (i) The use of one or two reductive plastered brace which enable a flow of the concavity ligaments; (ii) a moulding either hand-oriented or electronic after the resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 4 publications
2
20
0
Order By: Relevance
“…Casts have been included here as well. Casts are used by some schools as the first stage to achieve correction to be maintained afterwards with rigid brace [ 106 - 108 ]; others propose casting only in worst cases [ 92 , 93 , 109 , 110 ]; a cast is considered a standard approach in infantile scoliosis [ 111 ]. Recently, a new brace has been developed that has been claimed to achieve same results as casting [ 77 , 112 , 113 ].…”
Section: Evidence-based Clinical Practice Approach To Idiopathic Scolmentioning
confidence: 99%
“…Casts have been included here as well. Casts are used by some schools as the first stage to achieve correction to be maintained afterwards with rigid brace [ 106 - 108 ]; others propose casting only in worst cases [ 92 , 93 , 109 , 110 ]; a cast is considered a standard approach in infantile scoliosis [ 111 ]. Recently, a new brace has been developed that has been claimed to achieve same results as casting [ 77 , 112 , 113 ].…”
Section: Evidence-based Clinical Practice Approach To Idiopathic Scolmentioning
confidence: 99%
“…- Compliance, not defiance, is promoted through an evolution in the exercises which are repeated for a few minutes a day at home [7,8]. …”
Section: Contraindications To Brace Wearmentioning
confidence: 99%
“…Our hypothesis is that complete muscle relaxation, allows the surgeon to better derotate the spine while straightening it. Both rib vertebral angle difference and apical vertebral degree improved [17,[19][20][21][22][23][24]. Canavese et al showed that rib vertebral angle difference and apical vertebral degree are expression of vertebral rotation and can be used to better characterize the spinal deformity and/or to evaluate effects of brace or surgical treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…Both rib vertebral angle difference and apical vertebral degree improved [17,[19][20][21][22][23][24]. Canavese et al showed that rib vertebral angle difference and apical vertebral degree are expression of vertebral rotation and can be used to better characterize the spinal deformity and/or to evaluate effects of brace or surgical treatment [24]. However, the rib vertebral angle difference was originally described for children under the age of 2 years and its value for JS is not yet known [13,24].…”
Section: Discussionmentioning
confidence: 99%